A few factors in understanding French town planning - Terrin, Jean-Jacques (Raumforschung und Raumordnung | Spatial Research and Planning, 2008)
Current affairs have lately shone a less-than-flattering light on various events associated with French planning, but without giving much illumination to the reasons behind them. It is difficult to decode the deep-rooted causes of these phenomena without knowing about the historical, political and administrative context of French planning. We also need to understand the new political issues that are arising and the economic levers acting on a European scale, such as the emergence of new global private operators interacting with local contacts in terms of fundraising, management and urban design.